INTERRELATION OF ATHEROSCLEROSIS RISK FACTORS AND CENTRAL NERVOUS SYSTEM CONDITION IN PATIENTS WITH CHRONIC HEART FAILURE OF ISCHEMIC ORIGIN - N. S. Akimova; T. V. Martynovich; D. G. Persashvili; Yu. G. Shvarts (Кардиоваскулярная терапия и профилактика, 2014)
Aim. Chronic heart failure is one of the factors of the development and progression of cognitive disorders. To study the relationships between risk factors of atherosclerosis and condition of the central nervous system in patients with chronic heart failure of ischemic etiology.Material and methods. Cognitive tests, echocardiography, ultrasound investigation of carotid arteries, MRI of the brain and measurement of homocystein, CRP, lipid profile in venous blood were performed in 57 patients with I–IV functional class of chronic heart failure. Program STATISTICA7 (methods of incremental regression analysis) were used to assess the results.Results. Strong interactions between worsening of cognitive functions and increase of homocystein level, increase of thickness of IMC, decrease of low-density lipoprotein cholesterol were revealed. Decrease of thickness of the cerebral grey matter and increase of apparent diffusion coefficient of water molecules of the brain were associated with increased C-reactive protein levels, cholesterol of low density lipoproteins and high-density lipoproteins and with decrease of the thickness of carotid IMC. The decrease of thickness of middle legs of cerebellum was associated with reduced levels of low-density and high-density lipoprotein cholesterol.Conclusion. The relationship between risk factors of atherosclerosis, cognitive functions, and morphological changes of the brain was revealed.